Repenser l’étude génétique des œuvres cinématographiques - Emmanuelle Meunier (Mise au Point)
This paper aims at shedding light on the methods at stake in film genetic studies. Considering the genetics of a film may seem attractive if the amount of information at the researcher’s disposal is abundant. However the example of Casanova by Fellini reveals that one should remain circumspect with such plentiful information.